Literasi Dan Pelatihan Investasi Pasar Modal Bagi Komunitas Mobile Legend Pekanbaru - Ilham Hudi; Muhammad Ahyaruddin; Della Hilia Anriva; Mentari Dwi Aristi; Dian Puji Puspita Sari; Annie Mustika Putri; Nur Fitriana; Dian Hafiza Triana (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This activity provides an understanding to online game lovers about the importance of saving and investing from an early age and sharing other investment knowledge in the world of capital markets. This community service activity was carried out at the Semanggi Coffee Shop with participants, namely all members of the Pekanbaru Mobile Legend community. The result of this activity is that members of this online gaming community know and understand about the capital market and the products traded in the capital market. This service activity is carried out in several stages, namely at the initial stage the team conducts a briefing to prepare the materials and equipment needed, including: training materials, assignment letters, participant attendance lists, and consumption. In the final session, the activity was carried out by explaining the stock trading simulation using the IPOT application. When the simulation is carried out, participants see in real time the activity of stock trading transactions that occur on the Indonesian stock exchange.